Palynological analysis of the holocene section of a new core from Tswaing Crater, South Africa - Metwally, Amr Abdel-Sabour Abdel-Hamide (My University, 2011)
Palynological data from a new core from Tswaing Crater Lake within the savanna biome of South Africa contributes to a better understanding of vegetation and climate dynamics during the Holocene. A 650cm sediment core section TSW1, with 65 samples and fourteen AMS 14C dates, covers a time period between ca 10000-2000 cal yrs BP. No pollen data are available from the lower part of the profile (600-800cm) due to palynomorph destruction, but a single sample with a low number of pollen grains gives a glimpse into a presumably very dry time period at ca11300 cal yrs BP. A warm and dry early Holocene (ca 9000-7500 cal yrs BP) is evidenced by high pollen percentages of Asteraceae, Tarchonanthus and Dichrostachys. The mid Holocene phase from ca 7500-4000 cal yrs BP is characterised by an increase of Burkea, Combretaceae and Podocarpus as well as aquatics and swamp plant pollen. This suggests warm sub-humid conditions and local moisture during this time interval. A short-term dry period occurred ca 4000 -3600 cal yrs BP characterized by a significant decline of most tree pollen including Podocarpus, whereas Poaceae pollen increased slightly. From ca 3600 - 2000 cal yrs BP tree pollen percentages gradually increased and the presence of Spirostachys pollen suggests a return to warm sub-humid conditions. The upper part of the profile above a depth of 150cm shows disturbances due to salt mining and was therefore not sampled. The palaeoclimatic interpretation of the pollen fluctuations was supported by PCA (Principal Components Analysis). From around ca 1800 cal yrs BP additional samples were studied in this project in comparison to the previous study of Scott to improve the resolution. The climatic investigation from the Tswaing pollen record of the current study supports the climatic interpretations which were inferred from the biomarker analysis by Kristen et al., 2009. A regional comparison between the current Tswaing pollen profile and pollen records from Wonderkrater and Lake Eteza was done in the frame of the current study. The general palaeoclimatic changes recorded from Tswaing pollen sequence are consistent with the pollen evidence inferred from Wonderkrater which can attributed to regional changes in eastern South Africa. These trends differ from those in lake Eteza, especially during the early Holocene, which might be explained as a consequence of the generally more humid climate in the coastal plain of KwaZulu-Natal.